Recent Advances in Diagnosing Chronic Pulmonary Aspergillosis - Takazono, Takahiro; Izumikawa, Koichi (Frontiers in Microbiology, 2018)
Purpose The diagnosis of chronic pulmonary aspergillosis (CPA) is occasionally complicated due to poor sensitivity of mycological culture and colonization of Aspergillus species in the airway. Several diagnostic methods have been developed for the diagnosis of invasive pulmonary aspergillosis; however, their interpretation and significance are different in CPA. This study aimed to review the recent advances in diagnostic methods and their characteristics in the diagnosis of CPA. Recent findings Radiological findings of lung, histopathology, and culture are the gold standard of CPA diagnosis. Serodiagnosis methods involving the use of galactomannan and β-D-glucan have low sensitivity and specificity. An Aspergillus-specific IgG antibody assay showed good performance and had better sensitivity and reproducibility than conventional precipitant antibody assays. Currently, it is the most reliable method for diagnosing CPA caused by Aspergillus fumigatus, but evidence on its effectiveness in diagnosing CPA caused by non-fumigatus Aspergillus is lacking. Newly developed lateral flow device Aspergillus and detection of volatile organic compounds in breath have potential, but evidence on its effectiveness in diagnosing CPA is lacking. The increasing prevalence of azole-resistant A. fumigatus strains has become a threat to public health. Some of the azole-resistant-related genes can be detected directly from clinical samples using a commercially available kit. However, its clinical efficacy for routine use remains unclear, since resistance-related genes greatly differ among regions and countries. Conclusion Several issues surrounding the diagnosis of CPA remain unclear. Hence, further investigations and clinical studies are needed to improve the accuracy and efficiency of CPA diagnosis.